Movement and deformation of the Ordos basin and adjacent regions of North China - Peng Ding; Yuanjin Pan; Hao Ding; Jiashuang Jiao (All Earth)
The Ordos block is an important active block in North China during the Cenozoic and modern tectonic activity. Based on a large amount of GPS observation data, an accurate and dense GPS velocity field of the Ordos block is calculated through frame transformation. The results indicate that the estimated internal principal tensile and compressive strain rates of the Ordos block are 2.7 [Formula: see text] and 1.5[Formula: see text], respectively. Additionally, the block exhibits rigidity and there is negligible counterclockwise rotation. Relative to the Ordos Basin, the Loop Fault on the north side of the Ordos Block displays a left-rotation strike-slip rate of approximately 0.9 mm/yr and a dip-slip rate of around 0.5 mm/yr, accompanied by slight extrusion. The dip slip rate of the southern section of Taihang Mountain fault system indicates that there is spreading movement in the southeastern part of the block. The southwestern Liupanshan fault also experiences extrusive motion. These block motion features and fault sliding distributions provide a reliable database for understanding the possible motion and dynamics mechanisms of the Ordos region.